Traditional Medication – Rajah: The Rational Choice of Aceh People for Recovering Diseases during the Covid-19 Pandemic - Zainal, Suadi (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
This study aimed to explain the reasons of Aceh people's choice for nonmedical treatment - rajah during the Covid-19 pandemic. The qualitative approach was used to address the research problem. The findings showed that people chose nonmedical treatment with Rajah reading prayers and verses of the al-Quran then blowing on them and the water they brought to be drunk at their homes. They chose this treatment method by considering some rational reasons. Among the most prominent reasons; they were afraid to go to the government's public health service center for fear of being tested for antigens first and being judged to be positive for Covid-19, so they were quarantined and isolated from the community, both themselves and their families. In addition, Rajah was considered effective in curing diseases that resemble the symptoms of Covid-19, such as fever, flu, and cough. Even so, this study explains beyond the two reasons that are categorized as instrumental rational choices to achieve the goal – recovering from illness and avoiding threats of isolation. This study confirms that Aceh people put avoiding social isolation as the main rational choice in determining social action.Penelitian ini bertujuan untuk menjelaskan alasan pilihan masyarakat Aceh untuk berobat secara nonmedis – rajah di masa pandemi Covid-19. Pendekatan kualitatif digunakan untuk menjawab masalah penelitian. Temuan menunjukkan bahwa masyarakat memilih pengobatan nonmedis dengan membaca doa Rajah dan ayat-ayat al-Quran kemudian ditiupkan ke atas mereka dan air yang dibawanya untuk diminum di rumah masing-masing. Mereka memilih metode pengobatan ini dengan mempertimbangkan beberapa alasan yang rasional. Di antara alasan yang paling menonjol; mereka takut ke pusat pelayanan kesehatan masyarakat pemerintah karena takut dites antigen terlebih dahulu dan dinilai positif Covid-19, sehingga mereka dikarantina dan diisolasi dari masyarakat, baik diri sendiri maupun keluarganya. Selain itu, Rajah dinilai efektif menyembuhkan penyakit yang menyerupai gejala Covid-19, seperti demam, flu, dan batuk. Meski begitu, penelitian ini menjelaskan di luar dua alasan yang dikategorikan sebagai pilihan rasional instrumental untuk mencapai tujuan – pulih dari penyakit dan menghindari ancaman isolasi. Studi ini menegaskan bahwa masyarakat Aceh menempatkan menghindari isolasi sosial sebagai pilihan rasional utama dalam menentukan tindakan sosial.